Investigation into the influence of direct current (DC) power in the magnetron sputtering process on the copper crystallite size - CHAN, K; TEO, B (ELSEVIER SCI LTD, 2007)
This paper discusses the influence of direct current (DC) power in the magnetron sputtering process on the crystallite size of the copper (Cu) thin films deposited on p-type silicon substrate at room temperature. X-ray diffraction (XRD) and Karl Suss four-point probe were employed to study the film crystallinity and conductivity, respectively. From the analysis on the XRD patterns, high DC power enhances the Cu film crystallinity with larger crystallite size, which is deduced using Sherrer's formula. The behavior of the electrical property of the Cu films complies with the trend of the film crystallinity with DC power, in which the film conductivity increases with increasing DC power. We attribute these phenomena to the enhanced surface diffusion mechanism of the adatom during the sputtering deposition process, which improves the microstructure of the Cu film. (c) 2006 Elsevier Ltd. All rights reserved.